ANALISIS PENGARUH RELATIONSHIP BONDS , KEPUASAN KERJA TERHADAP KEPERCAYAAN DAN KOMITMEN - Cahya Purnama Asri; Utami Tunjung Sari; Rochmah Insani (Jurnal Bisnis Darmajaya, 2019)
This study examines the effect of relationship bonds, job satisfaction on trust and commitment in the relationship between producers and suppliers in the industry of Small and Medium Enterprises in Yogyakarta. Is there a positive influence between job satisfaction and trust, is there a positive influence between relationship bonds on commitment, is there a positive influence between job satisfaction on commitment and whether there is a positive effect of trust in commitment between producers and suppliers in the Micro Small Business industry Middle in Yogyakarta. The trust variable is influenced by one factor, namely job satisfaction. While for the commitment variable is influenced by three factors, namely job satisfaction, relationship bonds and trust. This research was conducted on industrial producers and suppliers of Small and Medium Micro Enterprises in Yogyakarta, the sample used in this study amounted to 50 respondents. The analytical tool used is multiple regression. The results of the study show that the relationship bonds variable, job satisfaction with trust has an influence on the commitment variable. From the study consisting of four hypotheses all were declared valid and positively affected.Keywords - relationship bonds, job satisfaction, trust, commitment, MSMEs.